"But for" percentages for economic development incentives: What percentage estimates are plausible based on the research literature? - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2018)
This paper reviews the research literature in the United States on effects of state and local "economic development incentives". Such incentives are tax breaks or grants, provided by state or local governments to individual firms, that are intended to affect firms' decisions about business location, expansion, or job retention. Incentives' benefits versus costs depend greatly on what percentage of incented firms would not have made a particular location/expansion/retention decision "but for" the incentive. Based on a review of 34 estimates of "but for" percentages, from 30 different studies, this paper concludes that typical incentives probably tip somewhere between 2 percent and 25 percent of incented firms toward making a decision favoring the location providing the incentive. In other words, for at least 75 percent of incented firms, the firm would have made a similar decision location/expansion/retention decision without the incentive. Many of the current incentive studies are positively biased toward overestimating the "but for" percentage. Better estimates of "but for" percentages depend on developing data that quantitatively measure diverse changes in incentive policies across comparable areas.
Keywords: R30; R12; H71; 330; Tax incentives; business location decisions; local economic development